Collaborative Mathematics and Statistics Research : Topics from the 9th Annual UNCG Regional Mathematics and Statistics Conference - Rychtář, Jan; Chhetri, Maya; Gupta, Sat; Shivaji, Ratnasingham (Springer Proceedings in Mathematics & Statistics, 2015)
This volume contains rigorously reviewed papers on the topics presented by students at The 9th Annual University of North Carolina at Greensboro Regional Mathematics and Statistics Conference (UNCG RMSC) that took place on November 2, 2013.  All papers are coauthored by student researchers and their faculty mentors. This conference series was inaugurated in 2005, and it now attracts over 150 participants from over 30 universities from North Carolina and surrounding states. The conference is specifically tailored for students to present their research projects that encompass a broad spectrum of topics in mathematics, mathematical biology, statistics, and computer science.